Breakfast skipping is associated with persistently increased arterial stiffness in patients with type 2 diabetes. Issue 1 (24th February 2020) - Mita, Tomoya; Osonoi, Yusuke; Osonoi, Takeshi; Saito, Miyoko; Nakayama, Shiho; Someya, Yuki; Ishida, Hidenori; Gosho, Masahiko; Watada, Hirotaka
Abstract : Objective: While certain lifestyle habits may be associated with arterial stiffness, there is limited literature investigating the relationship between lifestyle habits and longitudinal changes in arterial stiffness in patients with type 2 diabetes mellitus (T2DM). This is an exploratory study to determine whether lifestyle habits, in addition to conventional atherosclerotic risk factors, are associated with increased arterial stiffness. Research design and methods: The study participants comprised 734 Japanese outpatients with T2DM and no history of apparent cardiovascular diseases. Lifestyle habits were analyzed using self-reported questionnaires, and brachial-ankle pulse wave velocity (baPWV) was measured at baseline, and at years 2 and 5. A multivariable linear mixed-effects model was used to determine the predictive value of lifestyle habits and possible atherosclerotic risk factors for longitudinal change in baPWV. Results: Over 5 years of follow-up, baPWV values significantly increased. In a multivariable linear mixed-effects model that adjusted for age and gender, a low frequency of breakfast intake was significantly associated with persistently high baPWV, independently of other lifestyle habits. Furthermore, in a multivariable linear mixed-effects model that included both lifestyle habits and possible atherosclerotic risk factors, a low frequency of breakfast intake remained the only independent predictive factor for persistently high baPWV. Subjects who ate breakfast less frequently tended to have additional unhealthy lifestyle habits and atherosclerotic risk factors. Conclusions: Our analyses suggest that breakfast skipping is an independent lifestyle habit that is associated with persistently increased arterial stiffness in patients with T2DM. Trial registration number: UMIN000010932.